MEMBACA HERMENEUTIKA AL-QUR’AN MUHAMMAD IZZAT DARWAZAH - Kusmana Kusmana (Ushuluna: Jurnal Ilmu Ushuluddin, 2021)
This paper discusses Muhammad Izzat Darwazah (1887-1984)’s hermeneutics of the Qur’an. His thought is considered important because of his persistence in the view that the reconstruction of the initial context of Qur’anic revelation will bring the interpreter closer to the genuine message that Allah and his messenger Muhammad wanted to convey. Using a descriptive-analytic method, the writer portrays Darwazah’s thought position in both the development of tafsir as well as of tafsir nuzuli. In so doing, the writer outlines his discussion as follows introduction, basic structure of hermeneutics, examples of interpretation, status of Darwazah’s hermeneutics, and closing. This study finds that Darwazah’shermeneutic strength lies in the encyclopedic character of his work which provides rich information about the revelation of the Qur’an, the agencies involved, and the identification of early socio-religious processes and practices. Meanwhile, the weakness of his work lies in its entanglement in the hermeneutical burden, or in the expression of Wael Hallaq “Arabicate hermeneutics” which keeps Darwazah preoccupied with linguistic and historical discussion, while forgetting the focus and depth of the fundamental message of the Qur’an. Readers, instead of getting complete enlightenment, they overwhelmingly receive a variety of messages that are scattered, common sense and incomplete